Some Results in the Numerical Analysis of Structural Instabilities Part II. Dynamics - M. Kleiber (Engineering Transactions, 1982)
The paper is a direct continuation of the first part, [1], in which the application of the finite element technique to static stability problems was described and illustrated by a number of numerical examples. In this part of the paper some indications on how impulsive loading problems can be numerically analyzed with respect to the stability characteristics of motion are given. A step-by-step algorithm for the time integration of the nonlinear equations of motion is described and applied to different buckling prone structures subjected to uniform step loading of infinite duration.